Clinical manifestations and assessment of respiratory disease - Des Jardins, Terry R.; Burton, George G. , 1934- (Mosby Elsevier, 2016)
This popular, full-color text provides all the necessary tools you need to learn how to gather clinical data, formulate assessments, make objective evaluations, identify desired outcomes, design a safe and effective treatment plan, and document all the steps involved.And with a new chapter on respiratory failure and mechanical ventilation protocol, new information on electronic charting, and numerous updates in treatment and assessment added to nearly all the chapters, this new edition ensures you will be well-versed in all of the new issues affecting respiratory therapy